The Influence of Internal Communication and Work Motivation on Employee Performance at Central Events Kuta Bali - Desak Made Dwi Krisna Suryani Suryani; I Nengah Wirata; I Gusti Ngurah Agung Suprastayasa (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: This study aims to determine the effect of internal communication and work motivation on improving employee performance at Central Events. Method: The method of this research is quantitative, analyzed using Statistical Program for Social Science (SPSS) 25, with data analysis techniques using simple linear regression and multiple linear regression. Data collection was obtained from 33 respondents using saturated sampling through the distribution of questionnaires and documentation studies. Result: The results of the research partially showed that the internal communication variable had no positive and significant effect on employee performance with a value of tcount 1.226 < ttable 2.042 and a significance value of 0.230 > 0.05, meanwhile the work motivation variable had a positive but not significant effect on employee performance with a value of tcount 2.475 > ttable 2.042 and a significance value of 0.019 > 0.05. The results of the research simultaneously showed that the variables of internal communication and work motivation had a positive and significant effect on the performance of Central Events employees with a value of fcount 24.360> ftable 3.316 and a significance value of 0.000 <0.05. Contribution: Suggestions for improvement that can be given are that leaders should regularly hold meetings, make new policies to provide training and development on a regular basis and make policies that regulate working hours and sanctions for employees to create harmonious relationships, improve discipline, quality and employee performance..